Treatment of Industrial Effluents : Case Studies. - Purkait, Mihir K.; Mondal, Piyal; Chang, Chang-Tang (Boca Raton : CRC Press, 2019)
To address the issue of discharge of untreated industrial effluent in the water body causing pollution, adoption of cleaner production technologies and waste minimization initiatives are being encouraged. The book explains each related technology elaborately and critically analyses the same from practical application point of view. In-depth characterization, environmental and health effects and treatment of various industrial effluents are discussed with case studies. Limitations, challenges and remedial actions to be taken are included at the end of each chapter. Chapters are arranged as per specific type of effluents from various industries like textile, tannery/leather plant, and oil refinery.
Introduction to Different Industrial Effluents and Existing Treatment Technologies Treatment Techniques of Textile Plant Effluents Treatment of Leather Plant Effluents Treatment of Palm Oil Mill Effluents Treatment of Effluents from Sugar Processing Industry Treatment of Pharmaceutical Industry Effluents Treatment of Paper and Pulp Industry Effluents Effluent Treatment of Semiconductor Industry Treatment of Livestock Waste and Effluents Iron and Steel Industry Effluent Treatment Techniques Treatment of Coal Industry Effluents Treatment of Petrochemical Industry Effluents Treatment of Nuclear Industry Effluents Food Industry Effluent Treatment Techniques Technologies and Advancements for Gas Effluent Treatment of Various Industries
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Engineering / Chemical & Biochemical; SCIENCE / Chemistry / Industrial & Technical; Factory and trade waste; Sewage -- Purification